2012
DOI: 10.1016/j.cropro.2012.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Larval survival and plant injury of Cry1Ab-susceptible, -resistant, and -heterozygous genotypes of the sugarcane borer on transgenic corn containing single or pyramided Bt genes

Abstract: Fangneng, "Larval survival and plant injury of Cry1Ab-susceptible, -resistant, and -heterozygous genotypes of the sugarcane borer on transgenic corn containing single or pyramided Bt genes" (2012). Faculty Publications: Department of Entomology. 408.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 20 publications
1
27
0
2
Order By: Relevance
“…Several recent studies also showed that high levels of Bt resistance in target species of Bt crops can be nonrecessive, or even highly dominant. For example, a strain of D. saccharalis that was highly resistant to both purified Cry1Ab protein and Cry1Ab maize plants was found to be incompletely dominant on several commercial Cry1Ab maize hybrids with a D ML level of 0.32-0.78 (Ghimire et al, 2011;Wangila et al, 2012). The incompletely dominant inheritance character of the Cry1Ab resistance in D. saccharalis was also documented with Bt maize leaf tissue bioassays (Wu et al, 2007;Ghimire et al, 2011;Wangila et al, 2012).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Several recent studies also showed that high levels of Bt resistance in target species of Bt crops can be nonrecessive, or even highly dominant. For example, a strain of D. saccharalis that was highly resistant to both purified Cry1Ab protein and Cry1Ab maize plants was found to be incompletely dominant on several commercial Cry1Ab maize hybrids with a D ML level of 0.32-0.78 (Ghimire et al, 2011;Wangila et al, 2012). The incompletely dominant inheritance character of the Cry1Ab resistance in D. saccharalis was also documented with Bt maize leaf tissue bioassays (Wu et al, 2007;Ghimire et al, 2011;Wangila et al, 2012).…”
Section: Discussionmentioning
confidence: 74%
“…The SS-2009 strain was established from larvae collected from non-Bt maize plants in 2009 at the same location where the field population used for the F 2 screen was collected. SS-2009 is known to be susceptible to purified Cry1Aa, Cry1Ab, Cry1Ac, Cry1A.105, and Cry2Ab2 proteins, as well as, to Bt maize leaf tissue expressing Cry1Ab, Cry1A.105, and/or Cry2Ab2 proteins (Wangila et al, 2012;Zhang et al, 2013).…”
Section: Insect Collection and Establishment Of Two-parent Familiesmentioning
confidence: 99%
“…The three planting patterns were arranged in a randomized complete block design with a total of 5e7 replications for each trial (Table 1). Different planting patterns in a block were separated by one row distance (ca.1 m), and the distance between blocks was 3e4.5 m. Presence/absence of Bt proteins in Bt and non-Bt plants was validated using the same ELISA method as described in Wangila et al (2012).…”
Section: Bt and Non-bt Corn Hybridsmentioning
confidence: 99%
“…In addition, a known Cry1Ab-resistant strain (Cry1Ab-RR-2004) of D. saccharalis was also included in the bioassays in this study to serve as a positive control. Cry1Ab-RR-2004 was established from a field collection in 2004, which has been well documented to be highly resistant to both Cry1Ab-maize plants and purified Cry1Ab protein (Huang et al, 2007a(Huang et al, , 2007bWu et al, 2007;Ghimire et al, 2011;Wangila et al, 2012). Individuals of the seven resistant strains were backcrossed 2-3 times with individuals from the Cry1Ab-SS strain and re-selected for Bt resistance using leaf tissue from Cry1Ab expressing maize plants during the F 2 generations of the backcross.…”
Section: Sources Of Cry1ab-susceptible and -Resistant Strains Of D Smentioning
confidence: 99%